International Trade and the Business Cycle - Prasad, Eswar (IMF Working Papers; Working Paper, 1999)
This paper develops a new empirical framework for analyzing the dynamics of the trade balance in response to different types of macroeconomic shocks. The model provides a synthetic perspective on the conditional correlations between the business cycle and the trade balance that are generated by different shocks and attempts to reconcile these results with unconditional correlations found in the data. The results suggest that, in the post-Bretton Woods period, nominal shocks have been an important determinant of the forecast error variance for fluctuations in the trade balances of the Group of Seven countries.